A variationally coupled phase field and interface model for fracture in masonry. (May 2022) - Wambacq, J.; Ulloa, J.; Lombaert, G.; François, S.
Highlights: The phase-field approach to fracture is used to model fracture in masonry bricks. A non-associative softening plasticity model is adopted to model the mortar joints. The governing equations are rigorously derived in an energetic framework. A solution scheme based on an algorithmic decoupling of the equations is proposed. Four examples are considered and the results are compared to the literature. Abstract: This paper presents a computational model for unreinforced masonry structures, where softening plasticity describes the behavior of the mortar joints, while a brittle phase-field model accounts for fracture in the bricks. The governing equations are derived in an energetic framework, ensuring variational and thermodynamic consistency, while taking into account the non-associative behavior of the mortar joints, which allows capturing their experimentally observed low dilatancy. A numerical solution scheme based on an algorithmic decoupling of the governing equations is proposed for the rigorous solution of the quasi-static evolution problem. The presented methodology is applied to four numerical examples, showing that most of the fundamental masonry failure mechanisms are captured and complex crack topologies can be computed. In addition, the results are compared to both experimental data and numerical results reported in the literature.